Bilateral Fluctuating Sensorineural Hearing Loss as a Paraneoplastic Manifestation for Lymphoma - Young, Ting-Chia; Wang, Wen-Hsiu; Chu, Chia-Huei; Lin, Hung-Ching; Chen, Pey-Yu (The Laryngoscope, 2025)
Autoimmune inner ear disease (AIED) is an uncommon cause of fluctuating sensorineural hearing loss (SNHL), which is diagnosed by exclusion and required a high index of suspicion. Secondary AIED, which accompanies other autoimmune diseases, occurs in up to 30% of AIED cases. Secondary AIED is a rare manifestation of paraneoplastic syndrome, and the causal malignancy may be occult initially. Detecting and treating associated diseases, along with the use of immunosuppressants, are the mainstay for the management of AIED. Herein, we presented a woman with bilateral fluctuating and progressive SNHL, partially responding to steroid or immunosuppressant treatment. Her hearing eventually stabilized after completing the treatment for diffuse large B cell lymphoma, which was diagnosed 6 months after the onset of hearing loss. This case serves as a reminder to physicians to be aware of AIED in cases of fluctuating SNHL and the possibility of associated malignancy alongside autoimmune disturbance. Laryngoscope, 135:1496-1498, 2025.